Clinical Features of LMNA-Related Cardiomyopathy in 18 Patients and Characterization of Two Novel Variants - Valentina Ferradini (MDPI AG, 2021)
Dilated cardiomyopathy (DCM) refers to a spectrum of heterogeneous myocardial disorders characterized by ventricular dilation and depressed myocardial performance in the absence of hypertension, valvular, congenital, or ischemic heart disease. Mutations in LMNA gene, encoding for lamin A/C, account for 10% of familial DCM. LMNA-related cardiomyopathies are characterized by heterogeneous clinical manifestations that vary from a predominantly structural heart disease, mainly mild-to-moderate left ventricular (LV) dilatation associated or not with conduction system abnormalities, to highly pro-arrhythmic profiles where sudden cardiac death (SCD) occurs as the first manifestation of disease in an apparently normal heart. In the present study, we select, among 77 DCM families referred to our center for genetic counselling and molecular screening, 15 patient heterozygotes for LMNA variants. Segregation analysis in the relatives evidences other eight heterozygous patients. A genotype–phenotype correlation has been performed for symptomatic subjects. Lastly, we perform in vitro functional characterization of two novel LMNA variants using dermal fibroblasts obtained from three heterozygous patients, evidencing significant differences in terms of lamin expression and nuclear morphology. Due to the high risk of SCD that characterizes patients with lamin A/C cardiomyopathy, genetic testing for LMNA gene variants is highly recommended when there is suspicion of laminopathy.